Methodologic Approaches to Histologically Distinguishing Vaccine versus Nonvaccine-Associated Sarcomas Using Validated Time and Location Vaccination Histories in Cats. (14th September 2011) - Srivastav, Anup; Kass, Philip H.; McGill, Lawrence D.; Kent, Michael S.; Farver, Thomas B.
Abstract : Epidemiologic studies of feline vaccine-associated sarcoma (FVAS) require accurate sarcoma case definitions free from unverified assumptions for valid causal inference. This study developed methodologic approaches to improve reliable differentiation of vaccine versus nonvaccine-associated sarcomas on histologic characteristics using time windows of vaccine histories and body geographic information. Four case and five control definitions were used to classify 124 sarcomas. Results showed presence in the subcutis versus dermis, increased nuclear pleomorphism, more granulation tissue, and higher presence of inflammation in FVAS than presumptive non-FVAS. Correctly classifying sarcomas using stringent classification criteria as employed in this study will help reduce misclassification of FVAS in future epidemiologic studies of comparative risk.